Nanoporous activated carbon cloth as a versatile material for hydrogen adsorption, selective gas separation and electrochemical energy storage. (October 2017) - Kostoglou, Nikolaos; Koczwara, Christian; Prehal, Christian; Terziyska, Velislava; Babic, Biljana; Matovic, Branko; Constantinides, Georgios; Tampaxis, Christos; Charalambopoulou, Georgia; Steriotis, Theodore; Hinder, Steve; Baker, Mark; et al.
Abstract: The efficient storage of energy combined with a minimum carbon footprint is still considered one of the major challenges towards the transition to a progressive, sustainable and environmental friendly society on a global scale. The energy storage in pure chemical form using gas carriers with high heating values, including H2 and CH4, as well as via electrochemical means using state-of-the-art devices, such as batteries or supercapacitors, are two of the most attractive alternatives for the combustion of finite, carbon-rich and environmentally harmful fossil fuels, such as diesel and gasoline. A few-step, reproducible and scalable method is presented in this study for the preparation of an ultra-microporous (average pore size around 0.6 nm) activated carbon cloth (ACC) with large specific area (> 1200 m 2 /g) and pore volume (~ 0.5 cm 3 /g) upon combining chemical impregnation, carbonization and CO2 activation of a low-cost cellulose-based polymeric fabric. The ACC material shows a versatile character towards three different applications, including H2 storage via cryo-adsorption, separation of energy-dense CO2 /CH4 mixtures via selective adsorption and electrochemical energy storage using supercapacitor technology. Fully reversible H2 uptake capacities in excess of 3.1 wt% at 77 K and ~ 72 bar along with a significant heat of adsorption value of up to 8.4 kJ/mol for low surface coverage have been found. Upon incorporation of low-pressure sorption data in the ideal adsorbed solution theory model, the ACC is predicted to selectively adsorb about 4.5 times more CO2 than CH4 in ambient conditions and thus represents an appealing adsorbent for the purification of such gaseous mixtures. Finally, an electric double-layer capacitor device was assembled and tested for its electrochemical performance, constructed of binder-free and flexible ACC electrodes and aqueous CsCl electrolyte. The full-cell exhibits a gravimetric capacitance of ~ 121 F/g for a specific current of 0.02 A/g, which relative to the ACC's specific area, is superior to commercially available activated carbons. A capacitance retention of more than 97% was observed after 10, 000 charging/discharging cycles, thus indicating the ACC's suitability for demanding and high-performance energy storage on a commercial scale. The enhanced performance in all tested applications seems to be attributed to the mean ultra-micropore size of the ACC material instead of the available specific area and/or pore volume. Graphical abstract: Highlights: CO2 activation of carbonized viscose rayon leads to ultra-microporous carbon cloth. Strong interaction with H2 and reversible uptake of 3.12 wt% at 77 K and 72 bar. Predicted CO2 /CH4 gas selectivity factor of 4.5 at 298 K and 1 bar using IAST model. Excellent specific area normalized supercapacitor performance using CsCl electrolyte.